Getting started with STEAM practical strategies for the K-8 classroom - Krakower, Billy; Martin, Meredith (Educational trainer) (Routledge eye on education., 2019)
"Learn effective ways to teach STEAM with this helpful book from educational technology experts Billy Krakower and Meredith Martin. Whether you have a dedicated STEAM class, or plan to integrate it into a regular classroom, you'll find out how to create a structured learning environment while still leaving room for inquiry and innovation. You'll also gain a variety of hands-on activities and rubrics you can use immediately. Topics include: the differences among STEM, STEAM, and makerspaces; planning your STEAM space; stocking your space with the right supplies; planning for instruction and managing class time; incorporating the core subjects; aligning lessons with standards and assessments; getting the administration and community involved; taking your class to the next level with design thinking. With this practical book, you'll have all the tools you'll need to create a STEAM-friendly learning space starting now. Continue the conversation on Twitter with the hashtag #GSwSTEAM!" -- From the publisher.